If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = 2y + -3y + 4 Reorder the terms: 13 = 4 + 2y + -3y Combine like terms: 2y + -3y = -1y 13 = 4 + -1y Solving 13 = 4 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. 13 + y = 4 + -1y + y Combine like terms: -1y + y = 0 13 + y = 4 + 0 13 + y = 4 Add '-13' to each side of the equation. 13 + -13 + y = 4 + -13 Combine like terms: 13 + -13 = 0 0 + y = 4 + -13 y = 4 + -13 Combine like terms: 4 + -13 = -9 y = -9 Simplifying y = -9
| 5x^2-10x-80=0 | | 2(w-3)=3(w-1) | | 7k^2-6k*3=3 | | 32/4=b+4/3 | | 80+6x=145+7x | | 8=8n-4(a+8) | | .125d+7=16 | | 16a^2+24a+9= | | 2x-3y+z=-3 | | -3x^2+11x+25=0 | | 2x-1+6x=28 | | y=2x(4+3)-2 | | -11+z=6(z-4) | | 9v^2-121f^2= | | -7-2x-x=2 | | -6(1+3k)=-36-3k | | 2x^2-30x+75=0 | | x+6+2x=-x-4-2 | | 10p+4=-3+7p+1p | | -6(2x-3)+15=36 | | 9a^2+42at+49t^2= | | 5t+4=5+4t | | -6(2x-3)+15=33 | | -3(p+3)=-2(-2p-3)-2p | | [2x-7]=3 | | -2y+5x=12 | | 28n^2-96=-184n | | 5x-3=12+11 | | 7.4-5.3-9.2p=-2.6 | | 23+2= | | P=23+0.575x | | 25a^2-90a+81= |